2020
DOI: 10.14710/jpa.v2i2.7771
|View full text |Cite
|
Sign up to set email alerts
|

Electron contamination for 6 MV photon beams from an Elekta linac: Monte Carlo simulation

Abstract: In external beam radiotherapy, the photons from a linear accelerator (linac) machine undergo multiple interactions, not only in the patient but also in the linac head and the air column between the linac head and the patient. Electrons are released from these interactions and contaminate the beams. The current study evaluates electron contamination for 6 MV photon beams from an Elekta linac using Monte Carlo simulation. The linac head was simulated by the BEAMnrc code and the absorbed dose in a phantom was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The results of studies that had assessed the electron contamination sources in medical linear accelerators, indicated the flattening filters and air below the collimators, as two main sources of contaminating electrons for large radiation field sizes (24,36,42). Also, according to the results of reviewed article, the amount of electron contamination depends on the radiation field size (2,24,29,34,36,37,42) because for larger field sizes, the primary photons interact with more surface area of the collimator and air column between the linac head and the patient plane, which produces contaminating electrons and increases the surface dose (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies that had assessed the electron contamination sources in medical linear accelerators, indicated the flattening filters and air below the collimators, as two main sources of contaminating electrons for large radiation field sizes (24,36,42). Also, according to the results of reviewed article, the amount of electron contamination depends on the radiation field size (2,24,29,34,36,37,42) because for larger field sizes, the primary photons interact with more surface area of the collimator and air column between the linac head and the patient plane, which produces contaminating electrons and increases the surface dose (37).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they proposed that enough knowledge of the relative electron contribution specific to the measurement position and field size is required for measuring a 6 MV x-ray dose outside a field with a diode. The amount of contamination depends on the field size (2,24,34,36,38,42) and the energy of primary photons (26,31,32). Also, Narayanasamy et al declared that ion chamber readings when using 5, 10, and 15 mm bolus were about 31%, 22%, and 10% of the readings for open beam (30) Lye et al (33) showed that the lead cutouts applied for kilovoltage radiotherapy increase dose due to electron contamination at the edges of the radiation field at shallow depths.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to surgical treatment, external radiation therapy (EBT) is one of the proven treatment modalities for brain tumors. 2, 3 In this case, accurate radiation therapy planning is needed to increase conformity and sharp dose gradients beyond the target volume. This can improve the patient's quality of life because radiation doses to normal tissue with medium to high intensity have the potential for long-term toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The targets that are used to produce high-energy x-rays are those with high atomic numbers (high Z) such as tungsten, gold, silver, and tantalum (Vichi et al, 2020;Yeh et al, 2017). The resulting megavolt x-ray beam can be focused, directed, and uniformed using filters and collimators placed after the target (Anam et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sadrollahi et al (2019) using a Monte Carlo-based program, were able to determine the secondary electron energy of 0.1 MeV using a model of the Simen Premus LINAC machine. Anam et al (2020) using the Monte Carlo BEAMnrc-based program, were able to reveal the emergence of electron contaminants and the intensity of each component on the LINAC machine.…”
Section: Introductionmentioning
confidence: 99%